REKONSTRUKSI KONSEP PENANGGULANGAN TINDAK PIDANA DENGAN HUKUM PIDANA BERBASIS NILAI TRADISIONAL - Tongat Sidik Sunaryo (Masalah-Masalah Hukum, 2014)
Crime prevention through the means of criminal law is a dilemma. On the one hand, crime prevention through the means of criminal law is considered as the most rational effort role in crime prevention, while on the other hand, the negative impact of such complex social problems that lead to such extensive. Efforts to overcome the negative effects of the use of criminal law as a means of eradicating criminal acts continue to be made. One effort that can be an alternative is to integrate the criminal law and traditional values??in the response to crime. The use of traditional values ??as the basis of eradicating criminal acts continue to arise, as increasingly realizing the limited ability of the criminal law as a means of eradicating criminal acts. Integrating criminal law and traditional values ??as a means of eradicating criminal acts are also significant public role in the response to the presence of a criminal act, so that the state is no longer taking a central role in the response to the monopolistic crime